Meningkatkan Kesadaran Hipertensi Terhadap Lansia Melalui Edukasi dan Promosi Kesehatan Dengan Kegiatan Posyandu Lansia - Setiawan, Andika Putra; Pradana, Dicky Setiadi; Hidayat, M. Taufiq; Rozy, Muhammad Fahrur; Riswa, Gardiva Bintara (P3M Politeknik Negeri Jember, 2024)
Awareness of hypertension is becoming increasingly important in the elderly population due to its serious health implications. This study aims to identify the level of awareness about hypertension among the elderly through a literature review. Literature search methods were conducted through online databases such as PubMed, Google Scholar, and Scopus using relevant keywords. The results indicate that awareness of hypertension among the elderly varies significantly depending on factors such as education, knowledge level of risks, access to healthcare services, and cultural aspects. These factors influence the prevention behavior and management of hypertension in the elderly. Therefore, appropriate health education programs and interventions need to be introduced to enhance awareness of hypertension among the elderly. Further research is required to gain a deeper understanding of the challenges faced in increasing awareness and preventive actions against hypertension in the elderly population, thereby enhancing their quality of life and well-being.